Pelanggaran Batas Wilayah Laut Zona Ekonomi Eksklusif Oleh Nelayan Vietnam Dan Implikasi Hukumnya - Nur Aprilia Al Rasyid; Josina Augustina Yvonne Wattimena; Lucia Charlota Octavina Tahamata (PATTIMURA Law Study Review, 2023)
ABSTRACT: The South China Sea serves as the maritime boundary between Indonesia and Vietnam. Various issues that have arisen, especially in the Exclusive Economic Zone between Indonesia and Vietnam, are still unresolved to this day. In the last two years of 2021-2022, many foreign fishing vessels of Vietnamese fishermen have carried out illegal fishing activities in North Natuna Waters, where foreign fishing vessels of Vietnamese fishermen carry out fishing using pair trawling fishing methods which can damage fish resources. This resulted in Vietnamese fishermen violating Article 56 of UNCLOS 1982 concerning "Rights, jurisdiction and obligations of coastal States in the Exclusive Economic Zone". This research uses normative legal research methods using statutory approaches, conceptual approaches and case approaches. The legal materials used are primary and secondary legal materials and analyzed qualitatively. The result of this research is that illegal fishing activities carried out by foreign fishing vessels of Vietnamese fishermen can be qualified as a violation of the territorial sea boundaries of the Exclusive Economic Zone. And the legal implication is that both parties claim their right to implement the law in the region and claim each other's territory for the two countries that have not reached an international agreement regarding the Exclusive Economic Zone sea boundary. And this has an impact on the management of natural resources, defense, security, politics, social and economy, which can lead to conflict between the two countries.